Combination of monensin, virginiamycin, micro minerals and yeasts on biochemical profile of the blood and oxidative stress of the liver and meat of cattle fed a high-grain diet (Research, Society and Development, 2020)
This study was realized to evaluate the effect of monensin, virginiamycin and Advantage™ Confinamento (minerals traces + yeast) combination on blood hemogram, oxidative stress and antioxidant activity on blood plasma, liver and muscle. In total, 36 bulls (European vs. Nellore) were used, aged 24 ± 3.2 months and with an initial weight of 385.5 ± 3.84 kg, distributed in a completely randomized arrangement. The bulls were divided into four treatments according to their initial weight. The diet provided was based on concentrate (850 g/kg DM) and corn silage (150 g/kg DM) for 84 days. The diet composition was the same for all animals. The four diets were: CONT – without adding additives; MONE – inclusion of 30 mg/kg of dry matter of monensin; MO + VI – inclusion of 30 mg/kg of monensin + 30 mg/kg of dry matter of virginiamycin; MO + AD – inclusion of 30 mg/kg of monensin + 3.0 g/kg of dry matter of micro mineral and Saccharomyces cerevisiae (Advantage™ Confinamento). The biochemical profile of the blood was normal both at the start and at the final of the experiment. The oxidative stress of the liver had no difference in any evaluated parameter; however, in the muscle there was a difference in the enzyme glutathione peroxidase and in the group of carbonils protein. On oxidative stress of the plasma, the only difference was in the carbonils protein group. It was concluded that the monensin can be substituted by a combination of monensin + virginiamycin or monensin + Advantage™ Confinamento without generating oxidative damage in the tissues.